Preclinical support for tumor protein D52 as a cancer vaccine antigen - Robert K. Bright (Taylor & Francis Group, 2023)
ABSTRACTOverexpressed tumor-associated antigens (TAAs) are a large group that includes proteins found at increased levels in tumors compared to healthy cells. Universal tumor expression can be defined as overexpression in all cancers examined as has been shown for Tumor Protein D52. TPD52 is an over expressed TAA actively involved in transformation, leading to increased proliferation and metastasis. TPD52 overexpression has been demonstrated in many human adult and pediatric malignancies. The murine orthologue of TPD52 (mD52) parallels normal tissue expression patterns and known functions of human TPD52 (hD52). Here in we present our preclinical studies over the past 15 years which have demonstrated that vaccine induced immunity against mD52 is effective against multiple cancers in murine models, without inducing autoimmunity against healthy tissues and cells.